How Do We Know When an Enterprise Exists? Unanswerable Questions and Legal Polycentricity in China - Clarke, Donald C. (Columbia Journal of Asian Law, 2005)
One of the most perplexing aspects of Chinese enterprise law3 concerns the conditions under which state institutions will acknowledge and give effect to the existence of a business organization distinct from the natural or legal persons that participate in its operations. The answer might appear to be simple-they will do so whenever legally stipulated conditions are met-but this answer would be wrong. State institutions often give real and meaningful effect to the existence of entities with no apparent statutory basis, or whose legal basis dictates consequences that seem at odds with the consequences called for by constitutionally superior law. There can be no simple answer to the question of whether a business organization exists or not. Existence cannot be determined in the abstract. The answer must depend on the problem to be solved. For example, if the law requires a count of residents in a district, corporations do not exist at all. They are invisible to the law. But if the law requires a count of taxpayers, they suddenly reappear in front of the eyes of the state. We are accustomed to thinking of corporations and other business organizations as objectively existing because they are deemed to exist for many purposes. But it should be clear that there are many situations in which they do not exist-or at least, situations in which, like a ghost, they do not meaningfully interact with the world, in which case the question of whether they actually “exist” or not is metaphysical and uninteresting.